Cascade cycloadditions of N‐aromatic zwitterions and allylic sulfonium ylides: Dual roles of the allylic sulfonium ylide in the cascade reaction. (15th November 2022) - Jen, Hyundug; Yoo, Eun Jeong
Abstract: Dearomative cycloadditions of N‐aromatic zwitterions have been performed to synthesize diverse N‐containing cyclic compounds. However, few practical syntheses of polycyclic molecules are reported, and thus, a novel methodology is necessary. We describe cascade reactions of N‐aromatic zwitterions and allylic sulfonium ylides to furnish fused N‐heterocyclic compounds. Unprecedentedly, molecules of the allylic sulfonium ylide react with the corresponding zwitterion as C1 and C3 synthons in the same reaction. Abstract : We describe the cascade reactions of N‐aromatic zwitterions and allylic sulfonium ylides to furnish fused N‐heterocyclic compounds. Unprecedentedly, molecules of the allylic sulfonium ylide react with the corresponding zwitterion as C1‐ and C3 synthons in the same reaction.